2015
DOI: 10.5858/arpa.2014-0032-rs
|View full text |Cite
|
Sign up to set email alerts
|

Calcifying Fibrous Tumor of the Gastrointestinal Tract

Abstract: Calcifying fibrous tumor is a benign mass lesion classically described as a soft tissue tumor. However, a thorough review of the literature reveals that it can occur virtually anywhere, including the tubular gastrointestinal (GI) tract. Its clinical manifestations are variable in the GI tract, and its imaging findings are nonspecific. However, it has unique histologic and immunophenotypical features that must be recognized by GI pathologists to differentiate it from an assortment of other rare mesenchymal lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 29 publications
0
26
1
Order By: Relevance
“…The pathological findings of the mass in the present case were very different from those reported in the literature, with little cellularity and much hyalinization [6, 7]. In addition, mesenchymal cells only were present on the peripheral side of the mass.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…The pathological findings of the mass in the present case were very different from those reported in the literature, with little cellularity and much hyalinization [6, 7]. In addition, mesenchymal cells only were present on the peripheral side of the mass.…”
Section: Discussioncontrasting
confidence: 86%
“…Although previous studies reported calcific fibrous masses in the gastrointestinal tract [6] and inflammatory myofibroblastic tumors [7], there have been no published reports of a free mesenchymal mass in the abdomen, notably in men. The pathological findings of the mass in the present case were very different from those reported in the literature, with little cellularity and much hyalinization [6, 7].…”
Section: Discussionmentioning
confidence: 99%
“…1 Histologically they are defined by a triad of dense fibrosis, inflammation, and interspersed calcifications. 2 They are rare in the gastrointestinal tract and most gastrointestinal CFTs were reported as arising from the stomach. 1,3,4 CFT etiology is unknown, but it is thought to be the result of abnormal tissue healing, hence some authors refer to it as "calcifying fibrous pseudotumor."…”
mentioning
confidence: 99%
“…The differential diagnosis of a well-circumscribed pancreas tumor is broad. In our case, it was important to rule out metastatic carcinoma first and then consider gastrointestinal stromal tumor, solitary fibrous tumor, and inflammatory myofibroblastic tumor [5]. The differential diagnoses of gross and histologic pathology are discussed here.…”
Section: Discussionmentioning
confidence: 94%